Hubungan antara Self-Control dan Toxic Disinhibition Online Effect pada Mahasiswa yang Menggunakan Sosial Media - Ruli Gustian Nugraha; Kristin Rahmani; Heliany Kiswantomo; Dinta Nurannisa Aliifah; Alryami Rahma Pusti (Humanitas (Jurnal Psikologi), 2023)
The emergence of the internet in the current era has transformed the paradigm of students in their interactions, learning, and even coordinating collective actions. The Internet provides convenience in the exchange of ideas and information, as well as facilitating fast, easy, and accessible communication for various segments of society. New forms of social interaction through the internet have enriched both personal and social life on a broader scale. However, despite the significant constructive potential of the internet, there is another aspect that needs attention. The internet has the potential to reinforce communication behaviors that are inappropriate, less suitable, or even unrestricted, often referred to as the "toxic disinhibition online effect" (Suler, 2004; Lapidot-lefler & Barak, 2012). When students interact in social media connected to the internet, they may exhibit signs of a lack of self-control, where a lack of understanding of relevant social signals and disregard for rules and barriers in online interactions become the main factors in the emergence of this effect. This finding is reinforced by Joinson's research (2004), which revealed differences in individual behavior in the online and offline worlds, even in similar situations. This research was conducted to explore the relationship between the level of self-control and the "toxic disinhibition online" effect on students who actively use social media. Measurement was carried out using the Toxic disinhibition online effect scale and the Self-control scale. The research involved 154 student respondents, with the majority (86%) of them being female. A total of 50.6% of the respondents had a high level of self-control. However, the results of statistical analysis showed that there was no significant relationship between self-control and the "toxic disinhibition online" effect (p = 0.604, r = -0.042), with the significance value exceeding the 95% confidence level. In conclusion, this research did not find a significant relationship between self-control and the "toxic disinhibition online" effect among students using social media. These findings provide additional insights into student online behavior and its implications for self-control in the digital context. All of these findings contribute to understanding the role of the internet in the development of social and individual behavior in the digital age.